World Bank Research Digest, Vol. 13(2) - World Bank (World Bank, Washington, DC, 2019)
This issue focuses on Energy and features the following articles: Sustainable Energy Is Key to Achieving Global Development Goals; Charting the Diffusion of Power Sector Reforms across the Developing World; How Much Do Rural Households Benefit from Electrification? Evidence from Bangladesh; Forecasting Electricity Demand in Developing Countries: Is There a Better Way? Expanding Cross-Border Electricity Trade to Promote Hydropower in South Asia; The Nexus of Energy Supply and Human Health; Can Improved Biomass Stoves Be Cost-Effective in Mitigating Climate Change? Can Peer Pressure Encourage People to Adopt Energy-Saving Technologies? Solar Lanterns and Youth Academic Performance in Bangladesh; The Complexities of Integrating Renewable Energy into a Power System; and Interactions of Renewable Energy Standards with Carbon Emission Trading for Climate Change Mitigation.